Efficacy of Ginger (Zingiber officinale) and Celery (Apium graveolens L.) Extracts on Hair Growth in Wistar Rats (Rattus norvegicus) - Maylia Lie; Ali Napiah Nasution; Maya Sari Mutia; Rizki Arviandi; Eddy Sulistijanto (Ahmar Metastasis Health Journal)
Ginger (Zingiber officinale) and celery (Apium graveolens L.) are well-known for their anti-inflammatory and antioxidant properties, and they have been traditionally used to treat hair loss. However, scientific evidence regarding their effectiveness in stimulating hair growth is still limited. This study aims to evaluate the effects of ginger and celery extracts on hair growth in Wistar rats, focusing on growth onset, duration, regrowth, and potential inflammatory effects on the skin. The research method used a total of 25 Wistar rats randomly divided into five groups: control (paraffin), standard (minoxidil), ginger extract, celery extract, and a combination of ginger and celery extracts. Each extract was administered at a dosage of 20 mg/ml. The study monitored the onset, duration, and regrowth scores of hair growth. Histological examinations were performed to assess hair follicle density and inflammation levels. Phytochemical analyses of the extracts were conducted to identify the presence of flavonoids, alkaloids, glycosides, saponins, tannins, and steroids/triterpenoids. The research results show that phytochemical analysis revealed that ginger contains flavonoids, alkaloids, glycosides, and steroids/triterpenoids, while celery contains flavonoids, alkaloids, saponins, tannins, glycosides, and steroids/triterpenoids. The analysis showed no significant differences in hair growth onset, duration, or regrowth scores between the treatment groups and the control group. Histological analysis indicated that the average number of hairs ranged from 4 to 10 per field of view, with the highest count observed in the ginger extract group and the lowest in the celery extract group. Most slides showed light or no inflammation. The conclusion that the tested dosage, ginger and celery extracts did not have a significant impact on the onset, duration, or regrowth of hair in Wistar rats and showed minimal inflammatory responses. Although these extracts contain phytochemicals with known biological activity, they did not demonstrate significant effects on hair growth at the given dosage. Further research with different dosages and compounds is necessary to explore their full potential for hair growth and skin health.